Data Communication Via Bluetooth Between Pendrives Using Arm - Ashish, Abhijeet; Gautam, Gaurav; Sahi, Arjun (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
Now a days pendrive become so indespensible thing in our life. Any type of data is use share we need pendrive, to transfer those data first off all we need to put those datas in PC then into pendrive it is so hectic process so to overcome from this long process we need a pendrive with inbuilt bluetooth. By this pendrive we can share data directly from pendrive to pendrive without need of a PC. This is very effective process which can save time as well as effort of user.It will make user comfortable to share data eaisly. to work with this pen drive we need a small power supply to the pendrive almost 9 volt DC power supply. It can be dual means it can trasfer data usually with the help of PC or via bluetooth when power supply iven to it.